2014
DOI: 10.1016/j.amjoto.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal expression of aquaporin 5 and epithelial barrier proteins in chronic rhinosinusitis with and without nasal polyps

Abstract: Objectives The purpose of this study is to characterize the association between altered epithelial barrier function, represented by changes in histology and differential expression of the mucosal water membrane permeability protein aquaporin 5 (AQP5), and the pathophysiology of chronic refractory sinusitis (CRS) in patients with and without nasal polyposis. Study design Prospective clinical study. Setting Tertiary rhinology referral center. Participants Sinonasal samples were obtained from seven CRS subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 16 publications
(34 reference statements)
2
20
0
1
Order By: Relevance
“…This distribution is consistent with previous findings in humans (14,24). The subepithelial glandular cells are established to participate in mucus secretion and consistency, which maintain the function of the mucociliary system.…”
Section: Discussionsupporting
confidence: 93%
“…This distribution is consistent with previous findings in humans (14,24). The subepithelial glandular cells are established to participate in mucus secretion and consistency, which maintain the function of the mucociliary system.…”
Section: Discussionsupporting
confidence: 93%
“…Nasal polyp biopsy specimens showed decreased expression of TJ proteins, which also negatively correlated with disease severity and eosinophilic inflammation. It has been suggested that CRS barrier dysfunction is a result of environmental, microbial, and host factors . Previous research from our group has shown that the supernatants from S. aureus ATCC strain 13565 disrupt the TJs of HNEC‐ALI cultures; however, the identity of the toxin(s) responsible for this effect has yet to be identified .…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested that CRS barrier dysfunction is a result of environmental, microbial, and host factors. 4,34,35 Previous research from our group has shown that the supernatants from S. aureus ATCC strain 13565 disrupt the TJs of HNEC-ALI cultures; however, the identity of the toxin(s) responsible for this effect has yet to be identified. 9 This study does not exclude other S. aureus products as the responsible factor but rather highlights the protease family for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The group of Bachert reported that ZO-1, occludin and E-cadherin were all reduced in mature polyps removed from CRSwNP patients 51 . Moreover, aquaporin 5, a marker of epithelial differentiation, was significantly reduced in sinonasal samples of CRSwNP subjects compared to CRSsNP or controls 52 . Physical evidence of disruption of epithelial barrier in CRS includes prominent acanthosis and acantholysis 47 .…”
Section: Barrier Defects In Type 2 Diseasesmentioning
confidence: 88%